Lion & Sons Company furniture display - Gordon, John C. (photographer):::Creator::::::::::::
A living room display at Lion & Sons furniture store. The scene is filled wih chairs and sofas. There are light fixtures, an accent table, and a mock fireplace. The sign on the floor reads "Lion & Sons Co."